How industry experience can help in the teaching of entrepreneurship in universities - Liew, Yoke Ying * (Sunway University College, 2008)
The objective of this paper is to find out how industry experience can lend a hand in the delivery method for an Entrepreneurship course or subject. In this study, the method adopted is the focus group interview, wherein industry practitioners and entrepreneurs share their views on entrepreneurship education and the possible contribution of industry to the universities in grooming entrepreneurs. The findings reveal that entrepreneurs can be trained to a certain extent; internship is the main contribution by industry; and students? attributes are important foundation stones for moulding the students into entrepreneurs. In addition, there is a call for early training of entrepreneurship from primary school and family encouragement from young. The implication to universities is that teaching entrepreneurship as a subject means sharing knowledge with students while teaching it as a course should entail actual opportunities for students to set up businesses. Universities have to go beyond teaching and researching entrepreneurship and turn collaboration with industry into the catalyst for economic growth (Carlsson 2005).